KATA GANTI ORANG DALAM BAHASA INGGRIS DAN BAHASA TONSEA (SUATU ANALISIS KONTRASTIF) - MANDAGI, IRENE (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2018)
ABSTRACTÂ Â Â Â Â Â Â Â Â Â Â  Â Â Â Â Â Â Â Â Â Â Â  This research is entitled â€œKata Ganti Orang dalam Bahasa Inggris dan Bahasa Tonsea Suatu Analisis Kontrastifâ€. This research attempts to classify and analyze the Personal Pronoun in English and Tonsea Language and it is a research which focuses on syntactic analysis by looking at the case and function of personal pronoun. In classifying and analyzing the data, the researcher uses the theory of Aarts and Aarts (1982) and to contrast the data, she uses the theory of Lado (1975).Â Â Â Â Â Â Â Â Â Â Â  The results of this research show that English language have eight kinds of personal pronouns, namely: first person singular and plural, second person singular and plural, third person singular and plural. Third person singular is divided into three kinds those are: masculine, feminine, and netral. Tonsea language has six kinds of personal pronouns namely: first person singular and plural, second person singular and plural, third person singular and plural. The differences of both languages can be seen in third person singular. In English, third person singular is divided into three kinds by looking at the gender whereas in Tonsea is not. The position of the case in Tonsea language can be attached or separated after the noun and it can be a verb.Â Keywords: Syntax, Personal Pronoun, Case, Function, Contrastive Analysis: English, Â Â Â  Â Â Â Â Â Â Â TonseaÂ  Language.